Ratcheting fatigue of modified 9Cr-1Mo steel and Inconel alloy 617 at ambient temperature: Effect of uniform plastic strain - Mishra P.; Santhi Srinivas N.C.; Singh V. (My University, 2025)
Modified 9Cr-1Mo steel and Inconel alloy 617 (IN-617) are two important structural materials, used for piping/ tubing components in nuclear and advanced supercritical power plants. Such components undergo ratcheting fatigue, due to the mean stress, arising from fluctuations in temperature and internal pressure. This investigation presents dominant role of uniform plastic strain on ratcheting fatigue resistance comparing ratcheting fatigue life of these two materials under identical normalized mean stress and stress amplitude, at ambient temperature. Accumulated plastic strain in IN-617 was considerably higher than that of modified 9Cr-1Mo steel, although ratcheting fatigue life of IN-617 was much higher than that of modified steel. Higher uniform strain in IN-617 was found to be cause of observed behavior. Thus, uniform tensile strain of material can be considered as an important parameter for selection of materials to be used as tubular products in power plants, experiencing ratcheting fatigue. © 2022 Elsevier B.V.